KARTU KREDIT VS PAY LATER: PERAN LITERASI KEUANGAN DALAM MEMBAYAR PEMESANAN KAMAR HOTEL - Tiffani, Ignasia; Agung, Chris Petra; Dewi, Vera Intanie (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
The evolution of digital finance has led to payment innovations like paylater, an alternative to credit cards for credit transactions. One sector that provides both methods is hotel room booking through online travel agents (OTAs). This study examines the factors influencing the choice between paylater and credit card payment methods: financial literacy, digital literacy, and hotel characteristics. Employing multiple linear regression analysis, the research was conducted among residents of West Java and DKI Jakarta with paylater and credit card accounts. The results indicate that financial literacy and digital literacy significantly impact payment choices. Paylater embodies digital financial innovation in the era of Industry 4.0, while credit cards remain relevant in the ever-evolving digital financial ecosystem